2014
DOI: 10.5713/ajas.2014.14283
|View full text |Cite
|
Sign up to set email alerts
|

Association of DNA Methylation Levels with Tissue-specific Expression of Adipogenic and Lipogenic Genes in Longissimus dorsi Muscle of Korean Cattle

Abstract: Epigenetic factors, such as DNA methylation status, may regulate adipogenesis and lipogenesis, thus affecting intramuscular fat (IMF) deposition in longissimus dorsi muscle (LM) of beef cattle. In Korean cattle steers, the LM consists mainly of muscle tissue. However, the LM tissue also contains IMF. We compared the gene expression levels between the IMF and muscle portions of the LM after tissue separation. Real-time polymerase chain reaction analysis showed that the mRNA levels of both adipogenic peroxisome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 18 publications
0
18
0
2
Order By: Relevance
“…Understanding the factors affecting IMF deposition and the mechanisms responsible for its deposition is important when manipulating IMF deposition. Our laboratory has studied IMF deposition for more than a decade to understand the mechanisms responsible for IMF deposition in beef cattle [ 6 12 ], and we have reviewed molecular mechanisms responsible for IMF deposition in cattle [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the factors affecting IMF deposition and the mechanisms responsible for its deposition is important when manipulating IMF deposition. Our laboratory has studied IMF deposition for more than a decade to understand the mechanisms responsible for IMF deposition in beef cattle [ 6 12 ], and we have reviewed molecular mechanisms responsible for IMF deposition in cattle [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, DR did not affect the expression of several genes for lipogenesis (fatty acid-binding protein 4) and adipogenesis (peroxisome proliferator-activated receptor gamma and CCAAT/enhancer binding protein alpha) at both P1 and P2. Korean cattle steers accumulated significantly more body fat ( Bong et al, 2012 ; Baik et al, 2014 ). In our previous studies, bulls and steers had differential gene expression patterns for lipid metabolism, lipogenesis, and adipogenesis in the LM ( Bong et al, 2012 ; Jeong et al, 2013a , b ; Ahn et al, 2014 ; Baik et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…Korean cattle steers accumulated significantly more body fat ( Bong et al, 2012 ; Baik et al, 2014 ). In our previous studies, bulls and steers had differential gene expression patterns for lipid metabolism, lipogenesis, and adipogenesis in the LM ( Bong et al, 2012 ; Jeong et al, 2013a , b ; Ahn et al, 2014 ; Baik et al, 2014 ). Our study demonstrates that DR has minor effects on the expression of genes for lipid metabolism in the LM.…”
Section: Resultsmentioning
confidence: 99%
“…Examination of DNA methylation in adipose and muscle tissues of pigs showed that differentially methylated regions in gene promoters were highly associated with the development of obesity through repression of both known obesity-related genes and novel genes ( Li et al, 2012d ). Recently, Baik et al (2014) observed that DNA methylation status regulated tissue-specific expression of adipogenic and lipogenic genes in the intramuscular fat and longissimus dorsi muscle tissue in Korean cattle.…”
Section: Epigenetic Marks and Regulation Of Lipid Synthesis And Milk mentioning
confidence: 99%